State Medical Cannabis Laws Associated With Reduction in Opioid Prescriptions by Orthopaedic Surgeons in Medicare Part D Cohort. Issue 4 (15th February 2021) - Lopez, Cesar D.; Boddapati, Venkat; Jobin, Charles M.; Hickernell, Thomas R.
Abstract : Introduction: Opioid prescriptions and abuse remain a significant national concern. Cannabinoids offer a potentially attractive nonopioid analgesic option for orthopaedic patients, and 32 US states have passed medical cannabis laws (MCLs), legalizing patient access to cannabinoids. We examine the association between implementation of state cannabis laws and prescribing patterns for opioids by orthopaedic surgeons in Medicare Part D patients between 2013 and 2017. Methods: Using the Medicare Part D Prescription Drug Event database, we measured annual aggregate daily doses of all opioid medications (excluding buprenorphine) prescribed by orthopaedic surgeons in each US state (and DC), in addition to total daily doses of opioid medications by generic name (hydrocodone, oxycodone, fentanyl, morphine, methadone, and "other opioids"). We used adjusted linear regression models to examine associations between state-specific cannabis regulations (state MCL, MCL type—dispensary or home cultivation, and recreational cannabis legalization) and annual total daily doses of opioid medications (all opioids and opioid types, separately). Results: State MCLs were associated with a statistically significant reduction in aggregate opioid prescribing of 144, 000 daily doses (19.7% reduction) annually (95% confidence interval [CI], −0.535 to −0.024 million; P < 0.01). States with MCLs allowing access to in-state dispensaries had a statistically significant reduction in total opioid prescriptions of 96, 000 daily doses (13.1%) annually (95% CI, −0.165 to −0.026 million; P < 0.01). Specifically, MCLs were associated with a statistically significant reduction of 72, 000 daily doses of hydrocodone annually (95% CI, −0.164 to −0.019 million; P < 0.01). No significant association between recreational marijuana legalization and opioid prescribing was found. Conclusion: Orthopaedic surgeons are among the highest prescribers of opioids, highlighting the importance of providing nonopioid analgesic alternatives in efforts to reduce opioid use in the patient cohort. This study is the first to examine the association between implementation of state cannabis laws and prescribing patterns for opioids by orthopaedic surgeons in Medicare Part D patients. Level of Evidence: Population-based ecological study.